(untitled) (LEARNing Landscapes, 2021)
This paper examines the everyday creativity embedded within authentic classroom assessments. While not all authentic assessments are necessarily creative (i.e., novel, innovative, and contextually appropriate), I demonstrate everyday creativity in two authentic classroom assessments I have adopted in my TESOL courses. In revealing the everyday creativity of these tasks, and in light of their desired learning outcomes, I seek to demystify the role everyday creativity can play in student demonstrations of knowledge and skill.